2020
DOI: 10.1177/0300060520949072
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Effect of intersphincteric fistula tract ligation versus anal fistulectomy on pain scores and serum levels of vascular endothelial growth factor and interleukin-2 in patients with simple anal fistulas

Abstract: Objective This study was performed to explore the effects of ligation of the intersphincteric fistula tract (LIFT) on pain scores and serum levels of vascular endothelial growth factor (VEGF) and interleukin (IL)-2 in patients with simple anal fistulas. Methods Ninety patients with simple anal fistulas were evenly randomized into a study group (treated with LIFT) and a control group (treated with traditional anal fistulectomy) according to a random number table. The surgical outcomes, basic operation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In the previous study the mean pain score on postoperative day 1 between LIFT (6.72 ± 0.53) versus Fistulectomy (7.01 ± 0.56) ( p < 0.05), on postoperative day 3 LIFT (5.66 ± 0.11) versus Fistulectomy (6.01 ± 0.11) ( p < 0.05) and on postoperative day 5 LIFT (2.43 ± 0.24) versus Fistulectomy (3.51 ± 0.25) ( p < 0.05). The results of this study were in concordant to our study [ 14 ]. b) Postoperative pus discharge and bleeding Postoperative pus discharge and bleeding was noted at various intervals postoperatively in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In the previous study the mean pain score on postoperative day 1 between LIFT (6.72 ± 0.53) versus Fistulectomy (7.01 ± 0.56) ( p < 0.05), on postoperative day 3 LIFT (5.66 ± 0.11) versus Fistulectomy (6.01 ± 0.11) ( p < 0.05) and on postoperative day 5 LIFT (2.43 ± 0.24) versus Fistulectomy (3.51 ± 0.25) ( p < 0.05). The results of this study were in concordant to our study [ 14 ]. b) Postoperative pus discharge and bleeding Postoperative pus discharge and bleeding was noted at various intervals postoperatively in our study.…”
Section: Discussionsupporting
confidence: 93%
“…All things considered, in our study, postoperative pain incidence in the case of LIFT (2.81) is far less than in the case of fistulectomy (5.64). A study conducted by Xin Dong showed similar results of less pain experienced by the LIFT group than fistulectomy (p<0.05) 18 . However, in that study postoperative pain was assessed on the 1st, 3rd, and 5th post-operative days while we assess the patients on the night of surgery when the effect of spinal anaesthesia may persist.…”
Section: Discussionmentioning
confidence: 74%
“…García-Botello et al found that the severity of urinary incontinence increased with the complexity of the fistula ( 35 ). Dong et al showed that damage to the postoperative sphincter can lead to anal incontinence ( 36 ). Moreover, postoperative healing time for anal fistulas and anorectal abscesses is also a long process, requiring at least 3 months to recover ( 37 ).…”
Section: Discussionmentioning
confidence: 99%